Access to Oxoquinoline Heterocycles by N‐Heterocyclic Carbene Catalyzed Ester Activation for Selective Reaction with an Enone. (18th May 2014) - Fu, Zhenqian; Jiang, Ke; Zhu, Tingshun; Torres, Jaume; Chi, Yonggui Robin
Abstract: Organocatalytic ester activation is developed for a highly selective cascade reaction between saturated esters and amino enones. The reaction involves activation of the β‐carbon atom of the ester as a key step. This method allows a single‐step access to multicyclic oxoquinoline‐type heterocycles with high enantiomeric ratios. Abstract : Ein einstufiger enantioselektiver Zugang zu Multicyclen mit Oxochinolinmotiv profitiert von einem einzigartigen Reaktionsmuster von Estern in Gegenwart eines N‐heterocyclischen Carbens (NHC) als Katalysator. Auf die Aktivierung des Ester‐β‐Kohlenstoffatoms folgt eine chemoselektive Reaktionskaskade mit Aminoenonen. Ts=4‐Toluolsulfonyl.